Israel's Equal Rights for Persons with Disabilities Law: Current Status and Future Directions - Arie Rimmerman; Tal Araten-Bergman; Shirley Avrami; Faisal Azaiza (Disability Studies Quarterly, 2005)
Since the enactment of the Americans with Disabilities Act in the United States (1990), many countries have passed similar disability laws, shifting the focus from a social welfare approach to a human rights approach. Similarly, in 1998 the Israeli Knesset passed the first three sections of the new Equal Rights for Persons with Disabilities Law (Employment, Public Accommodations and Commission for Equal Rights of Persons with disabilities), leaving seven additional sections for future legislation. However, a thorough examination of its implementation reveals that the law has been only partially implemented, and there is concern as to whether this legislation brings a significant change in employment and social opportunities for people with disabilities in Israeli society. The article reviews and discusses the matter and suggests possible future directions for disability rights legislation.